Personal Health and Consumer Informatics - Gibbons, M. C. (Yearbook of Medical Informatics, 2013)
Objectives: The rapid evolution in the world-wide use of Social Media tools suggests the emergence of a global phenomenon that may have implications in the Personal Health and Consumer Health Informatics domains. However the impact of these tools on health outcomes is not known. The goal of this research was to review the randomized controlled trial (RCT) evidence of the impact of health oriented Social Media informatics tools on health outcomes.Methods: Evaluations of Social Media consumer health tools were systematically reviewed. Research was limited to studies published in the English language, published in Medline, published in the calendar year 2012 and limited to studies that utilized a RCT methodological design.Results and Conclusions: Two high quality Randomized Controlled Trials among over 600 articles published in Medline were identified. These studies indicate that Social Media interventions may be able to significantly improve pain control among patients with chronic pain and enhance weight loss maintenance among individuals attempting to lose weight. Significantly more research needs to be done to confirm these early findings, evaluate additional health outcomes and further evaluate emerging health oriented Social Media interventions. Chronic pain and weight control have both socially oriented determinants. These studies suggest that understanding the social component of a disease may ultimately provide novel therapeutic targets and socio-clinical interventional strategies.
Keywords: Social media; mHealth; consumer health informatics; randomized controlled trials; review